МАКТАБГАЧА ТАЪЛИМ МУАССАСАЛАРИ ТАРБИЯЛАНУВЧИЛАРИНИНГ ЖИСМОНИЙ РИВОЖИДА ЯНГИ АХБОРОТ ТЕХНОЛОГИЯЛАРИДАН ФОЙДАЛАНИШ МУАММОЛАРИ ВА ЕЧИМЛАРИ - Эшпўлатов, Ж.Н.; Мехмонов, Р.Ю. (SCIENCE and SOCIETY, 2019)
The article deals with the problems of using new information technologies in the physical development of preschoolers and the author gives solutions to these problems.
Keywords: pre-school education; physical development of the pupil; information-communication technologies; multimedia system